Image of Historical Persons in Stories - Razia Sadri (Indonesian Journal of Innovation Studies, 2022)
One of the main tasks of fiction is to create works dedicated to events that happened in the historical past, historical figures who lived in the recent or distant past. In contrast to scientific research, the writer effectively uses the text in a work on a historical subject, relying on the truth of history. Along with historical figures, the writer brings the image of textile heroes into the work in order to vividly embody the image of these people, to comprehensively illuminate the landscape of the depicted period.